Challenges Faced by Students in Authentic Speaking Assessment at SMA Swasta Santo Yoseph Medan - Khaira Cisadeva Marpaung; Neni Afrida Sari Harahap (Invention: Journal Research and Education Studies, 2026)
This study investigates the challenges experienced by students in authentic assessment of speaking skills and examines how these challenges influence their speaking performance. Speaking is considered one of the most important yet difficult skills in English learning, especially when students are required to perform in real communication tasks. The study was conducted at SMA Swasta Santo Yoseph Medan, involving 32 students of class XI-4. A qualitative descriptive design was applied to explore students’ experiences in depth. The data were collected through questionnaire as the main instrument, supported by interviews and classroom observation to strengthen the findings. The data were analyzed through data reduction, data display, and conclusion drawing. The findings reveal that students face several major challenges, including anxiety, lack of confidence, difficulty in organizing ideas, limited vocabulary, and confusion about assessment criteria. These challenges significantly affect students’ speaking performance by causing hesitation, reducing fluency, and making their speech less clear. In addition, classroom environment and time limitation also contribute to students’ difficulties. However, support from teachers and classmates, as well as clear understanding of assessment criteria, can help improve students’ performance. Therefore, it is important for teachers to create a supportive learning environment and provide clear guidance to help students perform better in authentic speaking assessment.